Pengaruh Sirkulasi Aliran Nutrisi Terhadap Produksi Sayuran Pakcoy Hidroponik: Pengaruh Sirkulasi Aliran Nutrisi Terhadap Produksi Sayuran Pakcoy Hidroponik - Nofriani Nofriani; Fedri Ibnusina; Alfikri Alfikri; Darnetti Darnetti (Journal Science Innovation and Technology (SINTECH), 2026)
Conversion of agricultural land triggers a decline in vegetable production, so it is necessary to optimize small areas of land through hydroponics. However, this system limits the high electricity costs caused by continuous pump circulation. This research aims to test the efficiency of regulating irrigation circulation on the growth of pakcoy plants in the DFT and NFT systems. The research method used a single factor Completely Randomized Design (CRD) with six water circulation treatment levels (24, 12, and 9 hours/day) and three replications. The parameters measured include morphological growth and plant fresh weight. Data were analyzed using ANOVA and Tukey's 5% follow-up test to determine the most efficient circulation treatment that still supports optimal growth. The research results obtained did not have a significant effect from testing 24 hour non-stop water circulation with intermittent flow of 12 hours and 9 hours, both in DFT and NFT system planting installations, on the growth and production of pak choy vegetables. Electricity costs for hydroponic cultivation can be saved by 50%-60% by setting the operating time of the water pump to only 9-12 hours, compared to turning it on continuously for 24 hours